2020
DOI: 10.1167/tvst.9.2.58
|View full text |Cite
|
Sign up to set email alerts
|

OCTA Multilayer and Multisector Peripapillary Microvascular Modeling for Diagnosing and Staging of Glaucoma

Abstract: To develop and assess an automatic procedure for classifying and staging glaucomatous vascular damage based on optical coherence tomography angiography (OCTA) imaging. Methods: OCTA scans (Zeiss Cirrus 5000 HD-OCT) from a random eye of 39 healthy subjects and 82 glaucoma patients were used to develop a new classification algorithm based on multilayer and multisector information. The averaged circumpapillary retinal nerve fiber layer (RNFL) thickness was also collected. Three models, support vector machine (SVM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…As this technology has progressed, a broad range of OCTA metrics were introduced to quantify microvasculature and aid in the diagnosis of glaucoma. Specifically, density parameters are used to track disease progression [18,[30][31][32][33] and more recent work has explored how changes in the macular regions, foveal avascular zone (FAZ), and deep retinal layer microvasculature contribute to disease severity [9].…”
Section: Optical Coherence Tomography Angiography In Glaucoma 31 Opti...mentioning
confidence: 99%
“…As this technology has progressed, a broad range of OCTA metrics were introduced to quantify microvasculature and aid in the diagnosis of glaucoma. Specifically, density parameters are used to track disease progression [18,[30][31][32][33] and more recent work has explored how changes in the macular regions, foveal avascular zone (FAZ), and deep retinal layer microvasculature contribute to disease severity [9].…”
Section: Optical Coherence Tomography Angiography In Glaucoma 31 Opti...mentioning
confidence: 99%
“…The standard modality of assessing structure, though, is OCT imaging; algorithms can provide assessment of the anterior chamber angle as well as segmentation of the RNFL adjusted for other parameters (age, gender, and eye biometry metrics) to improve the accuracy of the measurements ( 344 346 ). Studies have focused on many parameters of the retina and ONH (RNFL, prelaminar area, RPE, choroid, peripapillary sclera, Bruch membrane opening, and minimum rim width), and their performance was highly accurate in identifying glaucomatous eyes (>94%); AI analysis of OCT-A vascular abnormalities of the ONH also yields excellent results ( 347 354 ). When comparing various ML classifiers, Wu et al showed that ganglion cell layer measurements were important in early glaucoma detection, whereas RNFL metrics were more useful during disease progression; in fact, Shin et al showed that wide-field SS-OCT scans can even outperform the conventional parameter-based methods ( 355 357 ).…”
Section: Artificial Intelligence and Integrated Machine Learningmentioning
confidence: 99%
“…The Otsu method [17] is a commonly used automatic thresholding technique for OCTA images [18][19][20][21][22][23] and is based on finding a threshold that minimizes the intraclass variance of the thresholded black and white pixels. Other global thresholding methods are based on finding a specific percentile of the image intensity histogram [24], the progressive weighted mean of the image intensity histogram [25,26], or by simply fine-tuning a specific gray level [27]. Many analyzed studies employed a global thresholding technique without specifying exactly how the final threshold was determined [22,[28][29][30][31][32][33][34].…”
Section: Thresholdingmentioning
confidence: 99%
“…The most common machine learning method that was found for OCTA image classification was the support vector machine (SVM) [85]. This classifier was used for single disease detection, such as DR [70,84] and glaucoma [24,29], and was also employed for more complex classification tasks, such as DR staging [33] and distinguishing between different retinopathies [42]. The other classifiers that were used were NNs [32,83,86], k-means clustering [42], logistic regression [84], and a gradient boosting tree (XGBoost) [84].…”
Section: Machine Learningmentioning
confidence: 99%